Hubungan Antara Minat Belajar dengan Keterampilan Menulis Bahasa Jerman - Wahyu Mardyana; Syarifah Fathimah Al Ilmul; Hasmawati Hasmawati (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This study aims to obtain data on the relationship between interest in learning and writing skills in German class XI MAN 1 Makassar City. The variables in this study were students' interest in learning (X) with students' German writing skills (Y). The population in this study were students of class XI MIA MAN 1 Makassar with a total class of 7 classes and a total of 279 students, and the sample in this study was conducted randomly or Random Sampling, from randomly selected class XI MIA 1 MAN 1 Makassar totaling 39 students. The data from this study were obtained from a learning interest test with a German writing skill test. Based on the results of the Product Moment Correlation data analysis shows that r count is greater than r table (0,347 > 0,316). The results of data analysis showed that there was a significant positive relationship between interest in learning and writing skills in German in class XI MAN 1 MAKASSAR. Keywords: Interest in Learning, Writing Skills, German Language